Nickel Enhances Collagen-induced Platelet Activation Acting by Increasing the Organization of the Cytoskeleton - Pulcinelli, Fabio M.; Sebastiani, Silvia; Pesciotti, Marzia; Pignatelli, Pasquale; Gazzaniga, Pier Paolo; Daniel, James L. (Thrombosis and Haemostasis, 1998)
In keratinocytes, osteoclasts and enterocytes, Ni2+ acts as an agonist working through selective activation of the polyvalent cation-sensing receptor.We report here that while Ni2+ alone had no direct ability to induce platelet aggregation or secretion, Ni2+ pretreatment produced these responses when platelets were stimulated with subthreshold concentrations of collagen. In addition, pretreatment with Ni2+ significantly enhanced collagen-induced phospholipase C activation and calcium mobilization. Platelet adhesion to collagen was increased and the inhibition of collagen-induced adhesion normally seen after cytochalasin D treatment was significantly diminished.When Ni2+ was added to platelets alone, tyrosine phosphorylation of p60src was increased. Moreover, Ni2+ enhanced the amount of protein, especially actin, found in the low-speed Triton X-100 insoluble cyto-skeleton. Our results indicate that nickel, possibly acting via a platelet cation sensing receptor analogous to that which has been described in other cell types, may cause a rapid tyrosine kinase-dependent cyto-skeleton reorganization leading to enhanced adhesion of platelets to collagen and increasing collagen-dependent responses.